Novice drivers and parents: exploring the feasibility of third-party policing in reducing young driver offending - Belsham, David (Crime prevention and community safety, 2020)
Third-party policing involves police partnering with other individuals or organisations in order to prevent or control crime and disorder. Given the high level of young driver crash rates and offences, an intervention based on third-party policing may reduce both. This study explored the feasibility of using this approach with parents, who would be the third party, and young drivers in the Australian Capital Territory. Semistructured interviews with 16 parents and 11 of their children were conducted. The results suggest that given parents are supportive of the formal policing of young drivers and their willingness to impose additional restrictions on their children, that the introduction of an intervention based on a third-party policing framework is feasible. However, the lack of knowledge of GDL restrictions that apply to their child may make it difficult for parents to act as an enforcement authority in partnership with police. There is also the need to introduce a legal lever to support parents in their interactions with children and enable police to coerce parents into taking action.